Macronyssus diversipilis - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus diversipilis (Vitzthum, 1920) Liponyssus diversipilis Vitzthum, 1920: 23. Ichoronyssus diversipilis .— Fonseca, 1948: 299. Ichoronyssus blatnensis Dusbábek, 1964: 91 (synonymy by Radovsky, 1967). Macronyssus blatnensis .— Radovsky, 1966: 94. Macronyssus diversipilis .— Radovsky, 1966: 94; 1967: 127; Haitlinger, 1978: 711; Martyn, 1986: 137; Baker & Craven, 2003: 6; Bobkova, 2005: 75; Baker & Beccaloni, 2006: 173; Radovsky, 2010: 56. Type locality: Dockenhuden nr. Hamburg (Germany) (Vitzthum, 1920). Type host: Myotis daubentonii (Vitzthum, 1920). Material. N1 ex Myotis nattereri from State Nature Reserve “Samarskaya Luka”, 25 November 2001, leg. D.G. Smirnov; F, M ex Myotis daubentonii from State Nature Reserve “Samarskaya Luka”, 1-31 November 2005, leg. D.G. Smirnov; F ex M . daubentonii from State Nature Reserve “Samarskaya Luka”, 1-31 July 2006, leg. D.G. Smirnov; F (with intrauterinal egg), N1 ex M . brandtii from biological station “Preduraliye”, 24 July 2011, leg. O.L. Orlov, M. V. Orlova; 2 FF, 3 N1 ex M . daubentonii from Bolshoy Kizil river, 27 August 2014, leg. A. V. Zhigalin; 6 N1 ex M . daubentonii from Maliy Kizil river, 24 August 2014, leg. A. V. Zhigalin; 6 N1 ex M . daubentonii from Yangelka river, 21 August 2014, leg. A. V. Zhigalin; 5 FF, 3 MM, 21 N1 ex ex M . daubentonii from village Elimbetovo, 25 August 2014, leg. A. V. Zhigalin; 3 N1 ex M . nattereri from Serpievskaya cave, 30 October 2012, leg. O.L. Orlov; F, M, 2 N1 ex M . daubentonii from Arakaevskaya cave, 17 January 2010, leg. O.L. Orlov, M. V. Orlova. Distribution in Russian Federation: Russian Federation: Leningrad Province (Stanyukovich, 1990a; Stanyukovich, 1997), Samara Province (present paper), Udmurtia Republic (Orlova et al ., 2011), Dagestan Republic (Orlova et al ., 2020a), Bashkiria Republic (present paper), Sverdlovsk Region (present paper), Chelyabinsk Region (present paper), [European part of Russia, Pre-Urals, Urals— Orlova et al ., 2015d]. Distribution outside Russian Federation: Europe (Radovsky, ...